Spaceflight-Associated Vascular Remodeling and Gene Expression in Mouse Calvaria - Siamwala, Jamila H.; Macias, Brandon R.; Healey, Robert; Bennett, Brett; Hargens, Alan R. (Frontiers in Physiology, 2022)
Astronauts suffer from a loss of bone mass at a rate of 1.5% per month from lower regions of the body during long-duration (>30 days) spaceflight, a phenomenon that poses important risks for returning crew. Conversely, a gain in bone mass may occur in non-load bearing regions of the body as related to microgravity-induced cephalad fluid shift. Representing non-load bearing regions with mouse calvaria and leveraging the STS-131 (15-day) and BION-M1 (30-day) flights, we examined spatial and temporal calvarial vascular remodeling and gene expression related to microgravity exposure compared between spaceflight (SF) and ground control (GC) cohorts. We examined parasagittal capillary numbers and structures in calvaria from 16–23-week-old C57BL/6 female mice (GC, n = 4; SF, n = 5) from STS-131 and 19-20 week-old C57BL/6 male mice (GC, n = 6; SF, n = 6) from BION-M1 using a robust isolectin-IB4 vessel marker. We found that the vessel diameter reduces significantly in mice exposed to 15 days of spaceflight relative to control. Capillarization increases by 30% (SF vs GC, p=0.054) in SF mice compared to GC mice. The vessel numbers and diameter remain unchanged in BION-M1 mice calvarial section. We next analyzed the parietal pro-angiogenic (VEGFA) and pro-osteogenic gene (BMP-2, DMP1, RUNX2 and OCN) expression in BION-M1 mice using quantitative RT-PCR. VEGFA gene expression increased 15-fold while BMP-2 gene expression increased 11-fold in flight mice compared to GC. The linkage between vascular morphology and gene expression in the SF conditions suggests that angiogenesis may be important in the regulation of pathological bone growth in non-weight bearing regions of the body. Short-duration microgravity-mediated bone restructuring has implications in planning effective countermeasures for long-duration flights and extraterrestrial human habitation.